A Case of Intravascular Diffuse Large B-Cell Lymphoma Initially Suspected as Interstitial Pneumonia Associated With Systemic Scleroderma - Tomoyo Oguri MD, PhD; Shinji Sasada MD, PhD; Yuki Aramaki-Sumii MD; Yumi Tsuchiya MD; Kota Ishioka MD; Saeko Takahashi MD, PhD; Hisako Kunieda MD; Yoshifumi Kimura MD, PhD; Reishi Seki MD; Shigemichi Hirose MD, PhD; Morio Nakamura MD, PhD (SAGE Publishing, 2021)
Intravascular large B-cell lymphoma (IVLBCL) is a rare form of diffuse LBCL. The patient was a 71-year-old female admitted to our hospital with hypoxia. On admission, chest computed tomography revealed a ground-glass opacity. Interstitial pneumonia associated with systemic scleroderma was suspected because of positive anti-centromere antibody. Thereafter, steroid pulse therapy and plasma exchange were performed. Although ground-glass opacity improved, bilateral pleural effusion appeared, so we performed a random skin biopsy because of her elevated serum lactate dehydrogenase and soluble interleukin-2 receptor levels. The patient was diagnosed with IVLBCL with symptoms improving after 6 cycles of rituximab plus chemotherapy treatment.